CIVIL SOCIETY DALAM WAJAH KEISLAMAN DAN KEINDONESIAAN - M Zainal Abidin (Khazanah: Jurnal Studi Islam dan Humaniora, 2014)
This paper tries to explain the term of civil society according to Islamic and Indonesian perspectives. In Islamic view, the term of civil society was often paralleled with the term madani society, a term associated to the historical situation happened in the prophet era when agreed by the Medina people a charter named the Medina Charter as the foundation of acts of multi cultural and multi religious society in Medina. In Indonesian context, the term of civil society will be explained as a historical study of the struggling of Indonesian people to bring into reality the civil or medina society, especially after the fall down of New Order and the coming of Reformation Order. Before that, to make a comprehensive understanding about the term of topic, will b explained before the theoretical discourse on the term and the genealogy of civil society, whether happened among western scholars or Indonesian ones.